The Strategy of School Marketing in Admission New Students at MAS Ruhul Islam Anak Bangsa Aceh Besar District - Denni Aulia; Murniati Murniati; Nasir Usman (Yayasan Adra Karima Hubbi, 2023)
Background. Technological developments require educational institutions to design strategies in order to determine the target of students or people parents of the right students, so that educational institutions can make it easier to adjust between programs or activities produced with the goals of educational institutions. Purpose. Research objectives In general, students or parents will be interested in educational institutions that have several superior marketing factors such as the activity programs offered, strategic location, and adequate facilities and infrastructure to support the implementation of effective learning. Method. his research uses a statute approach. In addition, a case approach is also used to find out the ratio decidendi used by the Constitutional Court judges in deciding cases of judicial review of laws related to indigenous peoples. Results. The results of this study are Various kinds of efforts have been made by MAS Ruhul Islam Anak Bangsa in providing the best service to new students, one of which is by offering a special curriculum and offering about the achievements that have been achieved by MAS Ruhul Islam Anak Bangsa and proclaiming its vision, namely realizing Islamic, intellectual, and superior leaders in 1). Faith and piety 2). Science and technology. Conclusion. The conclusion is that technological developments require educational institutions to design strategies in order to determine the right target for students or parents of students